PERAN USAHA MIKRO KECIL MENENGAH (UMKM) TAHU DAN TEMPE DALAM PENINGKATAN EKONOMI KELUARGA: Usaha Mikro Kecil Menengah UMKM Tahu Dan Tempe Ibu Iis Di Desa Bangun Seranten Kecamatan Muara Tabir Kabupaten Tebo Provinsi Jambi - Solikah Hidarti; As’ad Isma; Hareastoma Hareastoma (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Qualitative research with the aim of seeing the role of Tofu and Tempe Micro, Small and Medium Enterprises (Mumkm). The results of the research show that the existence of Ibuk Iis tofu and tempe micro, small and medium enterprises (MSMEs) has a very big role for Bangun Seranten Village, especially in increasing employee income in these Micro, Small and Medium Enterprises (UMKM). The results of the interview show that this MSME not only provides permanent employment for the local community, but also provides a stable income for them or even greater than their income before working for this MSME. And also Ibuk Iis's tofu and tempe Micro, Small and Medium Enterprises (MSMEs) also face a number of challenges. One of the main problems is the difficulty of getting quality and affordable raw materials, coupled with tight competition for similar products. Complicated business licensing, complex financial administration, and so on.